2019
DOI: 10.1371/journal.pone.0224232
|View full text |Cite
|
Sign up to set email alerts
|

Fibre and extracellular matrix contributions to passive forces in human skeletal muscles: An experimental based constitutive law for numerical modelling of the passive element in the classical Hill-type three element model

Abstract: The forces that allow body movement can be divided into active (generated by sarcomeric contractile proteins) and passive (sustained by intra-sarcomeric proteins, fibre cytoskeleton and extracellular matrix (ECM)). These are needed to transmit the active forces to the tendon and the skeleton. However, the relative contribution of the intra- and extra- sarcomeric components in transmitting the passive forces is still under debate. There is limited data in the literature about human muscle and so it is difficult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 51 publications
6
35
0
Order By: Relevance
“…The techniques used could also provide empirical data to expand the capacity of current computational models of muscle stiffness (Marcucci et al . 2019; Bleiler et al . 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The techniques used could also provide empirical data to expand the capacity of current computational models of muscle stiffness (Marcucci et al . 2019; Bleiler et al . 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Critically, we also show that the alignment of these cables is significantly related to passive stiffness across genotypes and muscles, a general predictor of muscle stiffness. The techniques used could also provide empirical data to expand the capacity of current computational models of muscle stiffness (Marcucci et al 2019;Bleiler et al 2019). Collagen fibre alignment was indeed the most significant component of the ECM architecture-based model of muscle stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that the fiber network of ECM can be normalization and densification in the direction of force through stress-induced tension, which is conducive to muscle fiber contraction and cell migration [ 146 , 147 ]. Marcucci et al obtained the passive tension value of ECM fiber by subtracting the passive tension of muscle bundle and fiber, and then compared it with the passive tension of muscle fiber, proving that the modulus and tensile carrying capacity of ECM are higher than that of muscle fiber [ 148 ]. ECM hyperplasia can lead to the increase of stiffness and passive tension in skeletal muscles [ 149 ].…”
Section: The Roles Of Ecm In Skeletal Musclementioning
confidence: 99%
“…As discussed below, that is now thought to be incorrect, and that their throughplane shear properties are more important. Using finite element models based upon the Hill-type three-element model, Marcucci et al (2019) have recently suggested that the contribution to the parallel elastic component in passive muscle elasticity may nevertheless be substantial.…”
Section: Experimental Datamentioning
confidence: 99%